When Transparency Improves, Must Prices Reflect Fundamentals Better?. (25th April 2018) - Banerjee, Snehal; Davis, Jesse; Gondhi, Naveen
Abstract: No. In the presence of speculative opportunities, investors can learn about both asset fundamentals and the beliefs of other traders. We show that this learning exhibits complementarity: learning more along one dimension increases the value of learning about the other. As a result, regulatory changes may be counterproductive. First, increasing transparency (i.e., making fundamental information cheaper to acquire) can make prices less informative when investors respond by learning relatively more about others. Second, public disclosures discourage private learning about fundamentals, while encouraging information acquisition about others. Accordingly, disclosing more fundamental information can decrease overall informational efficiency by decreasing price informativeness. Received April 20, 2016; editorial decision September 30, 2017 by Editor Itay Goldstein.